On Experiencing a Hybrid Childhood in Times of Intensive Parenting - Research Results - Joanna Dziekońska (Maria Curie-Skłodowska University, Lublin, Poland, 2024)
Introduction: The progressive participation of media in children's lives determines the content of their experiences and contributes to the creation of new vision of childhood. Nowadays, it is implemented in unlimited digital space, however, with limited freedom in physical space. The resonance of changes is visible in many areas of children's lives and affects the way of their functioning.  Research Aim: The aim of the research was to show the aspects of experiencing childhood in a physical-digital world. The category of "experiencing" referred to the ways in which children function in interpenetrating offline and online spaces and to the emotions associated with it. Method: The method of collecting research material was focused group interviews, conducted among nineteen children aged 8-10. The method of data analysis was thematic analysis. Results: On the basis of the analysis, a map of themes and semantic codes was selected. The primary theme was "hybrid childhood", which included subtopics related to children's experience of modern childhood. The secondary topic was "intensive parenting", which referred to children's emotions aroused by their  disagreement with adults imposing on them visions of their own childhood. Conclusions: Children naturally enter the existing reality and move freely between traditional and network playgrounds, although they definitely notice the differences between them. Experiencing a hybrid childhood in the times of intensive parenthood is assosiated with the fact that children do not agree with the unjustified limits and restrictions related to being in the network imposed on them by parents, as adults do not adhere them themselves. Children express the need for autonomy and participation in making decisions about themselves. They contest arguments based on the common belief that adults have more rights than children.